2009
DOI: 10.2320/matertrans.m2009034
|View full text |Cite
|
Sign up to set email alerts
|

Time and Temperature Dependence of the Solubility of Carbon in Liquid Silicon Equilibrated with Silicon Carbide and Its Dependence on Boron Levels

Abstract: The solubility of carbon in liquid silicon equilibrated with silicon carbide has been studied in the temperature region 1414-1559 C. High purity silicon was melted in graphite crucibles under Ar atmosphere with various boron additions. The equilibrium was observed to be established within minutes, after which no evolution with time could be observed. The addition of boron to the system was found to increase the carbon solubility, and an equation was derived describing the solubility as a function of both tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 11 publications
2
18
0
Order By: Relevance
“…At the working temperature of 1500°C, silicon is in the liquid state and in equilibrium with SiC. Furthermore, according to literature data, the maximum value of carbon solubility into liquid silicon at 1500°C is found equal to 170 ppm in mass as shown in Figure 1-b) [19][20][21][22][23]. From this very low value, the interaction between pure molten silicon and SiC can be considered a priori as negligible.…”
Section: Background On the Capillary Infiltration Of Silicon Into Pormentioning
confidence: 77%
See 1 more Smart Citation
“…At the working temperature of 1500°C, silicon is in the liquid state and in equilibrium with SiC. Furthermore, according to literature data, the maximum value of carbon solubility into liquid silicon at 1500°C is found equal to 170 ppm in mass as shown in Figure 1-b) [19][20][21][22][23]. From this very low value, the interaction between pure molten silicon and SiC can be considered a priori as negligible.…”
Section: Background On the Capillary Infiltration Of Silicon Into Pormentioning
confidence: 77%
“…Figure 1. Si-C system: a) calculated Si-C diagram [18,19] and b) solubility of carbon in molten silicon from literature [19][20][21][22][23]. The values from Grobner et al were calculated by using ThermoCalc software [18].…”
Section: Resultsmentioning
confidence: 99%
“…That is why they were examined at 1600 1C by Eremenko et al [29]. Some other authors also examined the solubility of carbon in molten silicon [3,[30][31][32][33]. It is clear that carbon is very slightly soluble in molten silicon at 1450 1C (less than 100 ppm in mass) but all the studies indicate a noticeable increase with temperature (Fig.…”
Section: Introductionmentioning
confidence: 96%
“…The carbon solubility in liquid silicon has been determined by different authors, but the values differ in one order of magnitude, as shown by Dalaker and Tangstad. [1] These authors claim that the spread in the solubility values is a result of uncontrolled sources of carbon and oxygen, such as the crucible wall. Therefore, Dalaker and Tangstad [1] carried out carefully controlled experiments and obtained the carbon solubility in liquid silicon as 65 ppmw at the melting point 1687 K (1414°C).…”
mentioning
confidence: 99%
“…[1] These authors claim that the spread in the solubility values is a result of uncontrolled sources of carbon and oxygen, such as the crucible wall. Therefore, Dalaker and Tangstad [1] carried out carefully controlled experiments and obtained the carbon solubility in liquid silicon as 65 ppmw at the melting point 1687 K (1414°C). Therefore, approximately 90 pct of carbon in MGSi is combined in SiC particles.…”
mentioning
confidence: 99%